The Feasibility Analysis and Scheme Design of Raw Milk Price Index Insurance in China - Feng, Liyu (Archives of Business Research, 2017)
Dairy producers in China has been suffering from more and more frequently raw milk price fluctuations in recent years. Price Index insurance can be an effective tool of market risk management. We find that there are foreseeable trend, cyclical and seasonal factors in raw milk price fluctuations, and also systematicness in price risk, which make the raw milk price risk uninsurable. But by rationally designing the insurance scheme and institutional innovations, the price risks could become insurable. The choice and construction of milk price index are the core tasks of the scheme design. Income over feed cost could well reflect the actual profitability of milk production and is good to be used as milk price index. To prevent moral hazards and adverse selection, the contract should make stipulations on the coverage level from aspects of production covered and risk retention. We also carry a calculation of actuarially fair premium for the designed insurance contract using distribution approximation and Monte Carlo stimulation.